Antibiotic therapy duration for prosthetic joint infections treated by Debridement and Implant Retention (DAIR): Similar long-term remission for 6 weeks as compared to 12 weeks. (October 2017) - Chaussade, Hélène; Uçkay, Ilker; Vuagnat, Albert; Druon, Jérôme; Gras, Guillaume; Rosset, Philippe; Lipsky, Benjamin A.; Bernard, Louis
Highlights: A minority of all prosthetic joint infections are treated with the DAIR procedure. In prosthetic joint infections treated with the DAIR procedure, post-surgical duration of systemic antibiotic therapy after DAIR could be reduced to as short as 6 weeks. Abstract: Background: The required duration of antibiotic treatment for prosthetic joint infections (PJI) with debridement and retention of the implant (DAIR procedure) is unknown. Methods: Multicenter retrospective study emphasizing the duration of antibiotic therapy in patients treated with by DAIR. Results: We included 87 hip or knee PJI episodes in 87 patients from three university hospitals in France and Switzerland. All debridements were performed within 3 weeks of symptom onset. After a mean follow-up of 52.1 months, 60 patients with PJI (69%) remained in remission, with no significant difference between hip and knee cases (73.3% vs. 59.3%, 95% confidence interval (CI), 0.20–1.38), or between patients receiving 6 compared with 12 weeks of antibiotic treatment (70.5% vs.67.4%, 95%CI 0.27–2.10, p  = 0.60). Methicillin-resistant Staphylococcus aureus was isolated from 13.8% of infections and this was the only variable associated with a poorer outcome (remission in 41.7% vs. 73.3% for those with other pathogens, 95%CI 0.05–0.77, p  = 0.02). Conclusions: In patients undergoing DAIR for hip or knee PJI, the likelihood of long-term remission was not significantly different for those receiving 6 versus 12 weeks of antibiotic therapy. Prospective randomized trials are required to confirm this observation.